Phylogenomic Analysis of Oenococcus oeni Reveals Specific Domestication of Strains to Cider and Wines - Campbell-Sills, Hugo (Genome Biol Evol, 2015)
Oenococcus oeni is a lactic acid bacteria species encountered particularly in wine, where it achieves the malolactic fermentation. Molecular typing methods have previously revealed that the species is made of several genetic groups of strains, some being specific to certain types of wines, ciders or regions. Here, we describe 36 recently released O. oeni genomes and the phylogenomic analysis of these 36 plus 14 previously reported genomes. We also report three genome sequences of the sister species Oenococcus kitaharae that were used for phylogenomic reconstructions. Phylogenomic and population structure analyses performed revealed that the 50 O. oeni genomes delineate two major groups of 12 and 37 strains, respectively, named A and B, plus a putative group C, consisting of a single strain. A study on the orthologs and single nucleotide polymorphism contents of the genetic groups revealed that the domestication of some strains to products such as cider, wine, or champagne, is reflected at the genetic level. While group A strains proved to be predominant in wine and to form subgroups adapted to specific types of wine such as champagne, group B strains were found in wine and cider. The strain from putative group C was isolated from cider and genetically closer to group B strains. The results suggest that ancestral O. oeni strains were adapted to low-ethanol containing environments such as overripe fruits, and that they were domesticated to cider and wine, with group A strains being naturally selected in a process of further domestication to specific wines such as champagne.